Phased-inline coagulation for low-pressure membranes in water and wastewater treatment: a review of fouling mitigation, process control, and water quality - Ladouceur, Joseph D.; Narbaitz, Roberto M.; Lan, Christopher Q. (Environmental technology reviews, 2024)
Low-pressure membranes (LPM) are increasingly popular in water treatment due to their effective removal of microorganisms, pathogens, and protozoa. A more widespread implementation of LPMs in water treatment is prevented due to membrane fouling, which increases operating and maintenance costs. Coagulation pretreatment of the LPM feed water by continuous-inline coagulation (C-IN-C), which involves coagulant addition without particle separation prior to LPM filtration, is a commonly applied approach for fouling mitigation. Phased-inline coagulation (C-IN-P), a variant of C-IN-C where the coagulant is dosed inline for the initial portion of the filtration cycle, is the subject of increased interest due to the potential for significant cost savings through reduced coagulant usage. In this review, existing knowledge from pertinent publications regarding C-IN-P pretreatment of LPM feed waters is critically reviewed. Specifically, the C-IN-P approach is reviewed with emphasis placed on understanding fouling behaviour, process control, and the removal of organics. Available studies suggest that intermittent coagulant addition by C-IN-P pretreatment can achieve comparable fouling mitigation to C-IN-C, where coagulant is injected continuously. It has also been shown that C-IN-P can achieve similar removal of bulk organics measures to C-IN-C pretreatment for different water types, while also offering significant cost savings on coagulant. According to the knowledge gaps identified throughout the study, the manuscript concludes by outlining guidance on potential foci of future research.